Achieving transformation to lean management systems in health care. (24th October 2022) - Charns, Martin P.; Lerner, Barbara; Yakovchenko, Vera; Urech, Tracy H.; Shin, Marlena H.; Kim, Bo; Engle, Ryann L.; Vashi, Anita A.
Abstract: Objective: To understand what factors and organizational dynamics enable Lean transformation of health care organizations. Data Sources: Primary data were collected through two waves of interviews in 2016–2017 with leaders and staff at seven veterans affairs medical centers participating in Lean enterprise transformation. Study Design: Using an observational study design, for each site we coded and rated seven potential enablers of transformation. The outcome measure was the extent of Lean transformation, constructed by coding and rating 11 markers of depth and spread of transformation. Using multivalue coincidence analysis (CNA), we identified enablers that distinguished among sites having different levels of transformation. We identified representative quotes for the enablers. Data Collection Methods: We interviewed 121 executive leaders, middle managers, expert consultants, systems redesign staff, frontline supervisors, and staff. Principal Findings: Two sites achieved high Lean transformation, three medium, and two low. Together leadership support and capability development were sufficient for the three‐level Lean transformation outcomes with 100% consistency and 100% coverage. High scores on both corresponded to high Lean transformation; medium on either one corresponded to medium transformation; and low on both corresponded to low transformation. Additionally, low scores in communication and availability of data and very low scores in alignment characterized low‐transformation sites. Sites with high leadership support also had a high veteran engagement. Conclusions: This multisite study develops a novel measure of the extent of organization‐wide Lean transformation and uses CNA to identify enablers linked to transformation. It provides insights into why and how some organizations are more successful at transformation than others. Findings support the applicability of the organization transformation model that guided the study and highlight the roles of executive leadership and capability development in the dynamics of transformation.